THE EFFECT OF USING WORD WALL AND BAMBOOZLE GAMES IN SPEAKING SKILLS OF SEVENTH-GRADE STUDENTS - Irmawati Simangunsong; Erika Sinambela; Lastri Manurung (Merwin Publisher, 2024)
English is an international language that plays a large role in many spheres, not only the national but also the global. The purpose of this study is to assess the impacts of using Wordwall and Baamboozle apps on the improvement of English-speaking skills among junior high school students at SMPN 37 Medan. Both applications offer unique and interesting teaching-learning pedagogy that can perhaps lessen students apprehension towards speaking the foreign language as well as increase their interactiveness during learning. Using a quasi-experimental research design, this study involved a pre-test and post-test to assess students speaking skills before and after the intervention. Quantitative data taken from the speaking skills assessment showed that both apps can improve students speaking skills, with Baamboozle showing a more significant improvement. Data analysis used descriptive statistics and inferential statistics to compare pre-test and post-test scores to determine the improvement of speaking ability. The results of this study are expected to provide evidence supporting the effectiveness of gamification apps in language learning, as well as provide recommendations for educators to integrate technology in their teaching strategies.